2012
DOI: 10.1016/j.colsurfa.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic impregnation of porous anodic aluminum oxide film by silica nanoparticles

Abstract: h i g h l i g h t s ◮ Pores of an anodic film were completely filled by electrophoretic impregnation. ◮ Electric field and dispersion conductivity control the impregnation depth. ◮ Progressive filling from the bottom of pores to the top.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
(35 reference statements)
4
12
0
Order By: Relevance
“…The presence of some particles inside the pores would appear to result from the solvent drying, as already observed by some authors [35,36]. This result is consistent with what was reported by Fori et al [18] and argues in favour of using an electric field to improve the insertion of boehmite nanoparticles into the pores.…”
Section: 2a Impregnation Without Polarisationsupporting
confidence: 90%
See 1 more Smart Citation
“…The presence of some particles inside the pores would appear to result from the solvent drying, as already observed by some authors [35,36]. This result is consistent with what was reported by Fori et al [18] and argues in favour of using an electric field to improve the insertion of boehmite nanoparticles into the pores.…”
Section: 2a Impregnation Without Polarisationsupporting
confidence: 90%
“…Fori et al [18,19] responded to this issue by using an organic based dispersion of SiO 2 particles, leading to complete filling of the pores, thus successfully avoiding side reactions such as solvent electrolysis. Despite the difficulties encountered in using an aqueous medium for EDP, Kusdianto et al [20] reported the potential to fill pores of less than 1µm in length using a pulsed electric field to limit water splitting, while Escobar and al.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…FEG-SEM cross sectional views of the porous anodic oxide: (a) after electrophoresis process using 25 V/cm, (b) after electrophoresis process using 50 V/cm, and (c) after electrophoresis process using 200 V/cm. Electrophoresis -Life Sciences Practical Applications barrier layer at the metal-porous anodic film interface [15]. This finding is in satisfactory agreement with that of Fori et al [15].…”
Section: Electrophoretic Impregnation Of Anodic Coatingsupporting
confidence: 88%
“…Electrophoresis approaches using porous substrates based on anodic aluminium oxide (AAO) [20][21][22] or graphite [23] had been already reported with using non-aqueous media.…”
Section: Introductionmentioning
confidence: 99%